MID-TERM RESULTS OF AUTOLOGOUS MATRIX INDUCED CHONDROGENESIS (AMIC) IN CARTILAGE KNEE SURGERY. Issue 10 (10th June 2013) - Oheim, Ralf; Behrens, Peter; Volpi, Piero; Girolamo, Laura de; Reiss Eric, Edgar; Zoch, Werner; Anders, Sven; Gille, Justus
Abstract : Introduction: The regeneration capacity of articular cartilage is very limited. Therefore, cartilage defects heal poorly and are known as prearthrotic lesions. Autologous Matrix-Induced Chondrogenesis (AMIC) is an innovative treatment concept for localized full-thickness cartilage defects. This technique combines the well-established microfracturing with a collagen I/III scaffold fixated by fibrin glue. Methods: Presented are medium-term results of two different prospective studies of patients treated with AMIC. Symptomatic full-thickness cartilage lesions (Outerbridge grade III or IV) were treated using AMIC (Chondro-Gide, Geistlich Pharma, Switzerland). Patients were initially evaluated by established knee scores (e.g. Lysholm score, IKDC score) and in selected cases by magnetic resonance imaging (MRI). Patients were re-evaluated up to 5 years after the initial procedure. Results: In total 84 patients could be followed up. The average age of patients was in both groups 37 years (16–61 years). The mean defect size was 3.4 cm 2 respectively 4.2 cm 2 . The majority of patients were satisfied with the postoperative outcome, reporting a significant decrease of pain level. Significant improvement of the mean Lysholm score was observed as early as 1 year after AMIC and further increased values were noted up to two years postoperatively. MRI analysis showed moderate to complete filling with a normal to incidentally hyperintense signal in most cases. Conclusion: AMIC is an effective and safe method of treating symptomatic full-thickness chondral defects of the knee in appropriately selected cases. However, further studies with long-term follow-up are needed to determine whether the grafted area will maintain structural and functional integrity over time. Level of evidence: Prognostic study, Level IV.